Cefathiamidine-Induced Toxic Epidermal Necrolysis in a Child - QY, Wang; N, Zou; J, Zhu; MM, Zhang; ZJ, Liu (Archives of Clinical and Medical Case Reports, 2020)
Abstract not available in the source database.